Kepimpinan Strategis: Menciptakan Organisasi Pembelajar dan Organisasi Yang Beretika - Siti Nurul Kholillah; Azizah Salzabila; Hesti Kusumaningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In an increasingly complex and dynamic global landscape, strategic leadership plays a pivotal role in ensuring organizational resilience and sustainable growth. This study seeks to provide a meaningful contribution to the development of leadership strategies aimed at fostering both learning-oriented and ethically grounded organizations. Adopting a literature review approach, the research synthesizes a range of scholarly works to explore in depth the leadership practices that facilitate continuous learning while embedding ethical principles into organizational operations and culture.The analysis reveals that the essence of effective strategic leadership lies in the capacity to navigate rapid changes, exercise authority with wisdom, and cultivate a culture of integrity. Leaders who can anticipate and adapt to environmental shifts, while maintaining transparency and fairness, are better positioned to build trust and commitment within their organizations. Additionally, strategic leadership is found to be instrumental in shaping an environment that nurtures collaboration, stimulates innovation, and incorporates ethical considerations into all levels of decision-making.The findings underscore that leadership strategies must not only address operational and competitive challenges but also prioritize moral responsibility and collective well-being. This dual focus enables organizations to remain agile while preserving their ethical identity, thus strengthening their reputation and long-term sustainability.Ultimately, the study offers practical recommendations for leaders, particularly in the public and educational sectors, to design adaptive organizational systems rooted in ethical values. By integrating learning processes with moral governance, leaders can create a synergistic and sustainable framework that supports both organizational performance and societal trust, ensuring relevance and resilience in the face of continual change.